2023
DOI: 10.21608/ejnf.2023.298109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bee Venom on Production Performance and Immune Response of Broilers

Abstract: SUMMAYuring recent years, researchers evaluated many of eco-friendly alternatives to antibiotics such natural bee products as growth promoters in poultry production to improve the productive efficiency, modify the gut microflora, control diseases and enhancing the immune-response. The present study aimed at assessing the impacts of bee venom in drinking water on the growth performance, carcass merits, blood health, and immunity of broilers. Three hundreds and seventy five unsexed one-day old Avian chicks with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[29] Administered in drinking water up to 2 mg/L Boosts body weight, dressing percentage, carcass quality, and immunity of broilers. [44] Added at 2, 4, and 8 mg/kg body weight/day in drinking water…”
Section: Bee Products Administration and Dose Main Results Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] Administered in drinking water up to 2 mg/L Boosts body weight, dressing percentage, carcass quality, and immunity of broilers. [44] Added at 2, 4, and 8 mg/kg body weight/day in drinking water…”
Section: Bee Products Administration and Dose Main Results Referencesmentioning
confidence: 99%
“…Bee venom supplementation in drinking water (1 mg/L) had a substantial effect on broiler performance, including body weight, feed intake, and antioxidative capacity, especially during the early stages of life [96]. In the same manner, El-Banna et al [44] revealed that the use of bee venom in drinking water of broilers up to 2 mg/L can improve productive performance such as body weight, dressing percentage, and carcass traits as well as some internal organs (thymus, liver, and spleen). Bee venom can also stimulate and enhance chicks' immune responses by being injected with 0.5 mg/bird [97].…”
Section: Bee Venommentioning
confidence: 86%
“…Each experimental group received drinking water from individual containers. The selection of BV dosage was guided by prior research demonstrating improved growth performance and immune response in broiler chickens (El‐Banna et al, 2023; Han et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The BV compound was administered orally by incorporating it into the drinking water at concentrations of 0.5, 1 and 2 mg/L of drinking water every day for eight weeks. The dosage was established following the manufacturer's specifications and by considering pertinent research conducted by Han et al (2010) and El‐Banna et al (2023). The lyophilized purified BV used in this study was obtained from Umbrella Pharmaceuticals LLC.…”
Section: Methodsmentioning
confidence: 99%